Re/-Production: Identity, Queer, and Labor in the Work of Angela Mitropoulos - Pristovšek, Jovita (Identities: Journal for Politics, Gender and Culture, 2013)
The following paper analyses the status of identity, queer, and labor in relation to re-/production, as shown in the recently published book by Angela Mitropoulos, entitled Contract and Contagion. From Biopolitics to Oikonomia (2012). The aim of this paper is to suggest that oikonomia, as elaborated by Mitropoulos, is a biopolitical heterosexual oikonomia, where we should emphasize its necropolitical intensification that reaches beyond the border of the biopolitical, meaning that it literally breeds death (necro), or in other words, the state reproduces itself by extracting the surplus value from death and war machines. The above transformation will be – in reference to the formulation of Marina Gržinić – called “necropolitical intensification of biopolitics” – while at the same time pointing also to two triads of reproduction of capital/sex/labor and race that are the one of necessity/contingency/value and the other of debt/risk/law of value. My intention is to show how the sexual reproduction is incorporated into the capitalist system through the maximization of the theory of value. Author(s): Jovita Pristovšek Title (English): Re/-Production: Identity, Queer, and Labor in the Work of Angela Mitropoulos Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 20-28 Page Count: 9 Citation (English): Jovita Pristovšek, “Re/-Production: Identity, Queer, and Labor in the Work of Angela Mitropoulos,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 20-28.